1967
DOI: 10.1071/bi9670309
|View full text |Cite
|
Sign up to set email alerts
|

The Redistribution of Stem Sugars in Wheat During Grain Development

Abstract: SummaryIn wheat, a study of the distribution of 14C assimilated by single leaves near the time of anthesis showed that, during ear development, sugars previously accumulated in the stem internodes were in part redistributed to other plant organs and in part probably converted to polysaccharides within the stem. Only a small proportion of the stem sugar (including fructosans) was lost in respiration. Upward movement of sugar" occurred almost entirely from the top two internodes only. The contribution to the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…Although the early studies of Archbold (1942) on barley cast some doubt on the importance of stem reserves as a source of grain carbon it now appears that under well watered conditions these reserves, which include sucrose and a range of oligosaccharides, can be expected to account for 10-15 % of the weight of the grain at maturity (Wardlaw & Porter, 1967;Rawson & Evans, 1971;Austin et al, 1977). Blacklow, Darbyshire & Pheloung (1984) found that the maximum level of soluble carbohydrate occurred well into the grain development period (20-24 d after anthesis) and at this stage represented about 42 % of the stem dry weight.…”
Section: The Xylem As An Alternative Transport Systemmentioning
confidence: 99%
“…Although the early studies of Archbold (1942) on barley cast some doubt on the importance of stem reserves as a source of grain carbon it now appears that under well watered conditions these reserves, which include sucrose and a range of oligosaccharides, can be expected to account for 10-15 % of the weight of the grain at maturity (Wardlaw & Porter, 1967;Rawson & Evans, 1971;Austin et al, 1977). Blacklow, Darbyshire & Pheloung (1984) found that the maximum level of soluble carbohydrate occurred well into the grain development period (20-24 d after anthesis) and at this stage represented about 42 % of the stem dry weight.…”
Section: The Xylem As An Alternative Transport Systemmentioning
confidence: 99%
“…Furthermore, some estimates of movement to the grain are high as they do not allow for a proportion of the stem reserves to be transported to alternative sinks such as young developing tillers (Wardlaw & Porter, 1967). If a comparison is made later in kernel development between the rate of kernel filling and the mobilization of stem reserves over the same period, these reserves can account for 50% of the kernel requirements at this stage (Wardlaw & Porter, 1967 ;Apel & Na! tr, 1976 ;Bell & Incoll, 1990 ;Bonnett & Incoll, 1992).…”
Section: mentioning
confidence: 99%
“…Carbohydrates stored in the stem prior to anthesis may contribute 5-10% of final grain weight (Wardlaw and Porter 1967), or rather more in plants under stress (Asana and Joseph 1964;Yu et al 1964), but the major source of assimilate is current photosyr.thesis by the flag leaf, stem, and ear. The proportion of grain needs met by ear photosynthesis has been the subject of many investigations, reviewed by Thorne (1966).…”
Section: Introduotionmentioning
confidence: 99%